Short-term survival, space use and diel patterns of coastal fish species revealed from 'solo datasets'. Issue 2 (4th March 2021) - Mucientes, Gonzalo; Leeb, Katharina; Straßer, Fiona-Elaine; Villegas-Ríos, David; Alonso-Fernández, Alexandre
ABSTRACT: Individual acoustic tracking is a valuable tool to understand the behavioral ecology of aquatic species and to inform conservation actions. In this study, we examined the spatial behavior of single individuals of four common coastal fish species (striped red mullet, Mullus surmuletus ;corkwing wrasse, Symphodus melops ;pollack Pollachius pollachius ;and white seabream, Diplodus sargus ) in the National Park "Illas Atlánticas de Galicia" (NW Spain). The use of space of these species varied between 237, 975 m2 and 48, 725 m2, and the number of days that each fish was detected in the study area ranged between 35 and 110 days with weighted residence index ranged between 0.02 and 0.43. Pollackleft the array after 235 days, and was recaptured 342 days after tagging 10 km south from the study area. The movement of the studied species followed contrasting diel patterns. While white seabream and striped red mullet moved over larger areas during the day, pollackranged over larger areas during the night. This single individual study ('Solo datasets') represents a useful baseline for future research projects by providing preliminary knowledge of these poorly known species in the study area.